From Fatwa to Positive Law: Legal Certainty in Indonesia’s Sharia Governance Chain - Budi Dharma (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2026)
Indonesia’s Sharia governance chain operates within a dual financial system that separates institution-level supervision under the Financial Services Authority (OJK) from macroprudential oversight under Bank Indonesia, while Sharia compliance relies on DSN–MUI fatwas that must be translated into obligations under positive law. This article examines how legal certainty is formed, weakened, and repaired in the chain of Sharia governance from fatwa to positive law. Using doctrinal legal analysis, institutional mapping, and a bounded stress-test vignette from the Dana Syariah Indonesia case, the article shows that the central fragility of Sharia governance lies not in institutional absence but in the legal interfaces where fatwas must become regulatory obligations, institutional controls, supervisory evidence, escalation triggers, and enforceable remedies. The analysis identifies four main breakpoints: unclear translation from fatwa to regulatory rule, insufficiently specified evidence suitable for supervisory action, uncertain materiality thresholds for escalation, and limited Sharia-specific coordination when governance failures becomes conduct, prudential, reputational, or stability concerns. The article contributes to Islamic economic law by reframing Sharia governance as a legal certainty problem within Indonesia’s dual financial architecture. It proposes legally feasible improvements: a clearer fatwa to rule protocol, proportionate evidence standards, materiality-based escalation, remedial closure tests, and mandate-sensitive coordination across relevant authorities. Abstrak Rantai tata kelola syariah di Indonesia beroperasi dalam sistem keuangan ganda yang memisahkan pengawasan tingkat lembaga di bawah Otoritas Jasa Keuangan (OJK) dari kewenangan makroprudensial Bank Indonesia, sementara kepatuhan syariah bertumpu pada fatwa DSN–MUI yang harus diterjemahkan ke dalam kewajiban hukum positif. Artikel ini mengkaji bagaimana kepastian hukum dibentuk, melemah, dan dapat diperbaiki dalam rantai fatwa-ke-hukum positif pada tata kelola syariah. Dengan menggunakan analisis hukum doktrinal, pemetaan kelembagaan, dan vignette uji-tekan terbatas dari kasus Dana Syariah Indonesia, artikel ini menunjukkan bahwa kerentanan utama tata kelola syariah tidak terletak pada ketiadaan lembaga, tetapi pada antarmuka hukum tempat fatwa harus berubah menjadi kewajiban regulatif, kontrol kelembagaan, bukti yang layak-supervisi, pemicu eskalasi, dan remediasi yang dapat ditegakkan. Analisis mengidentifikasi empat titik rapuh utama: penerjemahan fatwa-ke-aturan yang belum jelas, standar bukti layak-supervisi yang belum kuat, ketidakpastian gerbang materialitas untuk eskalasi, dan terbatasnya koordinasi bertipe syariah ketika kegagalan tata kelola menimbulkan risiko perilaku pasar, prudensial, reputasi, atau stabilitas. Artikel ini berkontribusi pada hukum ekonomi syariah dengan membingkai tata kelola syariah sebagai persoalan kepastian hukum dalam arsitektur keuangan ganda Indonesia. Artikel ini mengusulkan perbaikan yang layak secara hukum: protokol fatwa-ke-aturan, standar bukti yang proporsional, eskalasi berbasis materialitas, uji penutupan remediasi, dan koordinasi antarlembaga yang sensitif terhadap mandat masing-masing.